Structural analysis of social behavior: Using cluster analysis to examine personality profile associated with diabetes onset - Anna Vespa; Roberta Spatuzzi; Paolo Fabbietti; Mirko Di Rosa; Maria Paola Luconi; Giorgio Arnaldi; Giancarlo Balercia; Gianmaria Salvo; Riccardo Sarzani; Maria Velia Giulietti (PLoS ONE, 2025)
Objective In this study we tested whether some intrapsychic behaviors of structure of personality can be associated with the onset of Type 2 diabetes (T2-DM). Methods T2-DM Patients (n. 257) and Healthy subjects (n = 258). Test: Social schedule (demographic variables); SASB–Form- Questionnaire A (describing intrapsychic behaviors of personality structure - 8 Clusters-Cl -). Results From the logistic model emerged that in subjects with profile 2 “Low Affiliation and Autonomy” compared to profile 2 “Low Autonomy and Self-Care” considering age, education and living conditions effects, the association to the onset of diabetes increases (OR: 1.668). Subjects with profile 2 “Low Affiliation and Autonomy” show low assertiveness and autonomy (SASB-Cl 1); have a medium-low ability to accept and support themselves (medium-low-SASB-Cl 3,4); do not improve their leisure activities or interpersonal relationships because they are too scheduled by things to do (SASB-Cl 4, Cl5); have self-critical behavior (SASB-Cl 6 medium) and self-neglectful behavior - ignore illnesses at an emotional and physical level (Cl8). They occasionally incur in self-destructive behaviors (Cl 7). They may experience self-exhaustion and mild to moderate depression. These are the intrapsychic behaviors associated with onset of diabetes. Another variable associated with the onset of diabetes is high educational level. Conclusions These results suggest that certain personality traits have a great association with T2-DM onset. Furthermore the analysis of intrapsychic modalities in association with the onset of diabetes could constitute a further screening aimed at primary prevention.